Robotic thoracic surgery versus video-assisted thoracic surgery for lung cancer: a meta-analysis - Ye, Xiong; Xie, Liang; Chen, Gang; Tang, Ji-Ming; Ben, Xiao-Song (Interactive cardiovascular and thoracic surgery, 2015)
OBJECTIVES There are two different minimally invasive approaches, robotic thoracic surgery (RTS) and video-assisted thoracic surgery (VATS), which are performed for lung cancer resection. This meta-analysis aimed to compare the perioperative outcomes of RTS with those of VATS for patients with lung cancer. METHODS We searched articles indexed in the PubMed and ScienceDirect databases that met our predefined criteria, published up to January 2015. A meta-analysis was performed by combining the results of reported incidences of perioperative morbidity and mortality. The relative risk (RR) was used as a summary statistic. RESULTS Eight eligible articles with 3379 subjects were considered in the analysis (8 articles for morbidity, while 4 articles for mortality). Overall, pooled analysis indicated that perioperative morbidity and mortality were similar between RTS and VATS (morbidity: RR, 1.02; 95% CI, 0.94–1.10; P = 0.605; mortality: RR, 0.28; 95% CI, 0.06–1.25; P = 0.095). No evidence of publication bias was observed. CONCLUSIONS This meta-analysis showed that RTS resulted in similar outcomes compared with VATS cases. RTS appears to be an appropriate alternative to VATS, which is associated with improved outcomes compared with open thoracotomy. RTS should be studied further in selected centres and compared with VATS in a randomized fashion to better define its potential advantages and disadvantages.